An alternative approach to inventory control and forecasting methods in the public and private sectors - Southworth, M. S. (Cranfield University, 1989)
This research was spawned by the questions and answers from the 33rd report of the committee of Public Accounts session 1983-84. The Key to the ensuing arguments about the report hinged on 3 words "Best Commercial Practice". In order to deduce a baseline the present systems of public and private concerns were investigated to find out what is actually being done. The thesis research examined what is actually happening today and in certain instances where companies have been prepared to speculate (and be open) what they believe they will be doing in the future. A review of the American and Germany Army systems has been included to ensure that the question 'best practice' could be examined between other systems having identical constraints^ The research includes both new and old literature by both academics and practitioners of the science of inventory. The hypothesis is that inventory is regarded in the singular whereas for all large concerns it should be considered in the plural, how the plural should be defined, what and how these sub inventories are and how they should be identified. The hypothesis whilst proven has the caveat that it only relates to inventories which are subject to similar structures and constraints. The effect of implementing the hypothesis in a working environment, possible areas for future work and research, largely due to the embryonic technical breakthroughs in information technology are examined briefly. The recommendations and conclusions represent an alternative approach to inventory control and forecasting not previously covered by either theoretical or practical work.